Development of a Student Basketball Game Model for State Elementary Schools 060891 Medan - Heka Mayasari br Sembiring (Journal Physical Health Recreation (JPHR), 2023)
Through observations conducted by researchers on January 8, 2016, at Sekolah Dasar Negeri 060891 Medan, it was seen that students were less active in learning physical education on basketball material. The inactivity is due to teaching materials that are not in accordance with the growth and development of students in teaching materials, especially basketball material, methods of use and equipment that are still not contained in teaching materials, so that the learning objectives are not achieved, in the basketball learning process that the authors get in the material basketball that has been known to students since elementary school. Based on these problems, the authors develop game teaching materials that please students through motion. The purpose of this research is to develop teaching materials in learning basketball fun. This type of research is development research and a sample of 20 students. The data have been collected and analyzed both quantitatively and qualitatively. Based on the research results obtained which are listed in the analysis and discussion section, it can be concluded that basketball game teaching materials for students of Sekolah Dasar Negeri 060891 Medan provide reliable and trusted teaching materials for intermediate level student teaching materials with a validity of 0.65. Reliability 0.60. Can be used as teaching material for basketball games for junior high schools.